«На острове Патмос»: отшельник С.И. Калмыков - Chudinovskaya, T.G. (Искусство Евразии, 2021)
The article is devoted to the work of Sergei Kalmykov, a Russian artist, illustrator, decorator, and writer. His art career started in the 1910s in Saint-Petersburg and later he called himself as “the last avant-garde of the first draft”, being aside of the mainstream of the development of Russian art. His free art was like a diary, like an endless dialog with himself. Each of his paintings from this monologue is a fragment tear out from one whole. The author interprets the painting “On the Island of Patmos” on the basis of an interdisciplinary approach that combines the principles of art history, cultural studies and mythopoetic analysis of a work of art. The study shows how complex his 'web' of creating thinking is and how it unexpected and deeply intertwined in one cultural field with other artists (Velimir Khlebnikov, Robert Lax) and even with religious images of almost two thousand years ago (John the Theologian). Статья посвящена творчеству Сергея Ивановича Калмыкова, русского художника, иллюстратора, декоратора, писателя. Начав свой творческий путь в 1910-е годы в петербургской художественной среде, он впоследствии сам себя называл «последним авангардистом первого призыва», оказавшись на задворках главенствующей линии развития отечественного искусства. Его свободное творчество представляло собой форму дневника, бесконечного одинокого разговора с самим собой. Каждая его картина из этого монолога — вырванный фрагмент из одного целого. На основе междисциплинарного подхода, сочетающего искусствоведческий, культурологический и мифопоэтический принципы анализа художественного произведения, автор статьи интерпретирует картину «На острове Патмос». Исследование демонстрирует, как сложна «паутина» творческого мышления, нити которого ткутся посредством художественного сознания и переплетаются самым неожиданным образом в общем культурном поле с другими творческими судьбами (Велимир Хлебников, Роберт Лакс) и даже с религиозными образами почти двухтысячелетней давности (Иоанн Богослов).